Determining The Timing For Harvesting Dried Apricot Products (Texas Journal of Agriculture and Biological Sciences, 2024)
The relevance of the topic, justification. As a result of the growing population in the world today, there are problems with the continuous provision of housing, drinking water, and food products throughout the year in some regions. In order for a person to live a healthy life, they must eat in accordance with medical standards. Meanwhile, the annual medical standards for the region's population include 58.3 kg of fruit products.